PENGARUH KELOMPOK SWABANTU DIABETES TERHADAP, PENGETAHUAN DAN KEPATUHAN KONTROL PASIEN DIABETES MELLITUS - mertha made (Jurnal Skala Husada : The Journal of Health, 2017)
Abstract.. DM patient empowerment in the form of self-help groups are very important in the management of diabetes management of patients with diabetes mellitus consisting of education, diet, physical activity, and medications. The research objective is to identify diabetes self-help groups, self-help kompok analyze the effect of diabetes on patients' knowledge of DM, and analyze the influence of self-help groups for compliance control diabetes patients with diabetes mellitus. This study is quasy-experimental with pre-post design without control group. The study was conducted at the health center IV South Denpasar for 5 months ie from June to October 2015. The study population was patients with DM and DM patients at high risk who went to the health center IV South Denpasar. Samples were selected that met the inclusion criteria and exclusion amounts to 35 people. Respondents subsequently formed self-help groups. Self-help groups in the form of counseling treatment diabetes management, prevention of the risk of diabetes, foot care, foot gymnastics, yoga activities and random blood sugar measurements once a month. Data collection tool was a questionnaire about their knowledge and compliance controls are carried out pre and post treatment. Based on the results of statistical tests revealed no influence of self-help groups for knowledge and compliance control of diabetic patients at the health center IV South Denpasar (p = 0.000; α = 0.05). Researchers suggest that the self-help groups that have maintained and improved type of activities.Keywords: self-help groups, diabetes mellitus, knowledge, compliance Abstrak. Pemberdayaan pasien DM dalam bentuk kelompok swabantu diabetes sangat penting dalam managemen pengelolaan pasien DM yang terdiri dari edukasi, diet, aktivitas jasmani, dan obat. Tujuan penelitian adalah untuk mengidentifikasi kelompok swabantu diabetes, menganalisa pengaruh kompok swabantu diabetes terhadap pengetahuan pasien DM, dan menganalisa pengaruh kelompok swabantu diabetes terhadap kepatuhan kontrol pasien DM. Penelitian ini merupakan penelitian quasy-experimental dengan rancangan pre post without group control. Penelitian dilakukan di Puskesmas IV Denpasar Selatan selama 5 bulan yaitu bulan Juni sampai Oktober 2015.  Populasi penelitian adalah pasien DM dan pasien risiko tinggi DM yang berobat ke Puskesmas IV Denpasar Selatan. Sampel yang dipilih yang memenuhi kriteria inklusi dan eklusi berjumlah 35 orang. Responden selanjutnya dibentuk kelompok swabantu. Perlakuan kelompok swabantu berupa penyuluhan penatalaksanaan DM, pencegahan risiko DM, perawatan kaki, senam kaki, kegiatan yoga dan pengukuran gula darah acak sebulan sekali. Alat pengumpul data berupa kuesioner tentang pengetahuan dan kepatuhan kontrol yang dilakukan pre dan post perlakuan. Berdasarkan hasil uji statistik dinyatakan ada pengaruh kelompok swabantu terhadap pengetahuan dan kepatuhan kontrol pasien DM di Puskesmas IV Denpasar Selatan (p= 0,000 ; α=0,05). Peneliti menyarankan agar kelompok swabantu yang sudah teerbentuk dipertahankan dan ditingkatkan jenis kegiatannya.Kata kunci: kelompok swabantu, diabetes mellitus, pengetahuan, kepatuhan